Survival for Ten Years after Aggressive Surgery for Pericardial Recurrent Thymoma with Proton-Beam Radiation Therapy for An Unresectable Intramyocardial Lesion: A Case Report - Fukai, Ryuta; Irie, Yoshihito; Akimoto, Tetsuo; Akasaka, Keiichi; Nakano, Kentaro (Archives of Clinical and Medical Case Reports, 2020)
There is no standard treatment for recurrent thymoma, although complete surgical resection reportedly achieves significantly better survival than other treatments. However, surgical treatment of recurrent thymoma in the pericardium is challenging because of the serious surgical stress and the adverse cardiac effects incurred by opening the pericardial space. We treated a female patient with a recurrence of thymoma 5 years after a complete response to radical radiotherapy. We removed the intrapericardial thymoma under cardiac arrest using an artificial-heart lung apparatus; however, we aborted our attempt to remove another intramyocardial lesion overlapping the left circumflex coronary artery. By 3 years after surgery, the residual intramyocardial tumor had increased in size, so we provided proton-beam radiation therapy. The patient has been well for 10 years after surgery with no sign of recurrence. We should consider aggressive treatment for patients in good general health, even for recurrent thymoma in the pericardium. Proton therapy might be effective for unresectable lesions because it appears to minimize damage to cardiac function. <gdiv></gdiv>